Tinjauan Historis Kewenangan Penyelesaian Perselisihan Hasil Pemilihan Umum (PHPU) Dan Perselisihan Hasil Pemilihan (PHP) Oleh Mahkamah Konstitusi (MK) - Hidayatullah, Hidayatullah; Lestanata, Yudhi; Darmansyah, Darmansyah (Jurnal Ilmiah Mandala Education (JIME), 2022)
One of the real forms of change based on the will to create a democratic government is the establishment of the Constitutional Court as a judicial institution formed with the aim of maintaining the implementation of constitutional values in the implementation of state life. With the Constitutional Court, currently the judicial power in Indonesia is run by two institutions, namely the Supreme Court and the Constitutional Court. The birth of the Constitutional Court itself is an answer to the desire that judicial institutions can conduct legal testing of the Constitution that previously could not be done, but the number of cases of disputed election results that entered the Constitutional Court also raises a new question, because is it right for the Constitutional Court to decide the dispute over the election results which is actually a political matter?. This writing will use normative research methods. Research is conducted by conducting searches on legal materials, books, journals and scientific articles both published both domestically and abroad. Furthermore, from the sources obtained, analysis is carried out using qualitative juridical analysis methods. The results of the study resulted in an analysis related to the authority of the Constitutional Court to decide the case of Disputed Election Results and Disputed Election Results where this authority before the formation of the Constitutional Court is still not clear to which institution will decide the case.